Genetic variation for nitrogen-Use efficiency among selected tropical maize hybrids differing in grain yield potential (2012)
Low soil nitrogen (N) and sub-optimal N fertilizer applications result in poor grain yield (GY) in maize. Genotypes with improved N-use efficiency (NUE) are particularly beneficial to low-input agriculture. Information on the relative importance of the main components of NUE will facilitate genetic improvement of tropical maize for NUE. This study evaluated genetic variation for NUE among tropical maize hybrids selected for contrasting responses to N. The hybrids were grown in replicated trials from 2006 to 2008 where plots received either no (0 kg N/ha), low (30 kg N/ha), or high (90 kg N/ha) levels of supplemental N. The results documented significant genetic variation for GY and measured NUE component traits among the hybrids, as well as significant interactions between hybrid and N level for all traits except nitrogen harvest index. Under low N, NUE, NUPE, and NUTE increased by 61%, 21%, and 42%, respectively. Grain yield was significantly and positively correlated with NUE, NUPE, and NUTE at both low N and high N. Both NUPE and NUTE were significantly and positively correlated to NUE. Five hybrids (4001/4008, KU1409/4008, KU1409/9613, 4008/1808, and 1824/9432) produced similar GY at both low N and high N but differed in their NUPE and NUTE. Genetic variation was present among the maize hybrids studied for NUE and its components. Although both NUPE and NUTE contributed to high grain yield, the relative importance of the two traits to NUE varied with genotype and level of N.